Examining The Effect of Digital Skills, Computer and Smartphone Usage Hours on The Digital Impact Among Students in A Malaysian Public University - Razana Juhaida Johari; Norfadzilah Rashid; Nor Hafizah Abdul Rahman; Rina Fadhilah Ismail; Yusarina Mat Isa (Universitas Pasundan, 2024)
The objective of this study is to examine the digital impact among undergraduate students in a Malaysian public university that focus on how digital skills, computer and smartphone usage hours influence students perceived digital impact. This study involves a quantitative methodology, sampling 204 undergraduate students from a Malaysian public university. The use of an online questionnaire format facilitated widespread distribution, made completion more convenient for respondents, and facilitated the accumulation and management of responses. The results demonstrate a strong sense of digital citizenship among the respondents. Variables such as hours spent on the computer (COMPHOUR), digital skills (DIGSKILL), and hours spent on the smartphone (HPHOUR) have varying degrees of impact on the dependent variable, the perceived digital impact (DIGIMPACT). DIGSKILL appears to have a significant relationship with DIGIMPACT but not the HPHOUR and COMPHOUR. The findings underscore the importance of digital skills and call for the development of comprehensive digital literacy programs to equip students with the necessary skills for responsible and meaningful engagement with digital technology. This study added to the literature by analyzing digital skills, computer and smartphone usage hours on the digital impact among university students in Malaysia.